METHODOLOGY FOR TRAINING SUBJECTS BASED ON AN INTEGRATIVE APPROACH (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
The article discusses the problems of enhancing the cognitive activity of students at the stage of pre-university preparation and a number of tasks aimed at developing and improving the learning process when preparing students for entering a university.